ナンキョク ニ オケル フウリョク ハツデンキ カイハツ ノ イギ ト ニホン ナンキョク チイキ カンソク タイ ガ シヨウ シタ ジッケンキ ノ モンダイ テン - 石沢, 賢二; イシザワ, ケンジ; Ishizawa, Kenji (1988)
P(論文) 日本南極地域観測隊がこれまで利用を目指してきた風力発電機の用途は, 無人観測用の電力源と, 基地の雑用電力源とである。無人観測用保温箱の熱源としては, 太陽電池も有効だが極夜の約2カ月は発電不能で, 風力発電に期待がかかる。しかし, これには大きな電力は必要なく, 10W以下の発電能力で十分である。また, 輸送距離の長い内陸基地で風力発電機を雑用電力源として使用すると, 燃料輸送量の節減に大きく役立つ。南極昭和基地(69°00′S, 39°35′E)とみずほ基地(70°42′S, 44°20′E)での風況曲線のデータより, 風力発電で期待される発電量を計算した。日本の南極地域観測隊が実験・使用してきた風力発電機の故障原因を調べた結果, 南極特有の厳しい気象条件よりも, 風力発電機そのものの研究不足によるブレードの振動等の根本的な事柄が多いことがわかった。 Wind generators have been used and tested by the Japanese Antarctic Research Expedition (JARE), to supply power for unmanned observatories and for heaters at the stations. A solar battery is also effective as a heat source of the thermally insulated box for unmanned observation, but the battery fails to work for about two months in winter. Therefore, a wind generator is necessary to make up for the powerless winter months. Even a small power of the wind generator less than 10W is sufficient for this purpose. The use of a wind generator as a domestic power source at an inland station will reduce amount of fuel to be transported to the station over a long distance. The expected power of the wind generator at Syowa Station (69°00′S, 39°35′E) and Mizuho Station (70°42′S, 44°20′E), Antarctica, was calculated by using the wind utilization curves at the two stations. The troubles of many wind generators JARE used in Antarctica were found to have resulted not from severe weather conditions but from fundamental matters such as vibration of blades. Studies of the wind generator itself are required in the first place, before it is put to use in Antarctica. departmental bulletin paper